Complete chloroplast genome of Angelica keiskei (Umbelliferae). Issue 2 (1st February 2021) - Yan, Wen-Jie; Yang, Tian-Ge; Qin, Rui; Liu, Hong
Abstract: Angelica keiskei (Miq.) Koidz. is a perennial herbaceous plant belonging to the genus Angelica, Umbelliferae. As a plant with dual-purpose as food and medicine, it has the potential for the future development of high-value functional products. The complete chloroplast genome has a total size of 147, 007 bp, consisting of two inverted repeats (IR, 18, 508 bp, each), and separated by a large single-copy region (LSC, 92, 415 bp) and a small single-copy region (SSC, 17, 576 bp). Further annotation revealed the chloroplast genome contains 128 genes, including 84 protein-coding genes (80 PCG species), 36 tRNA genes (30 tRNA species), and 8 rRNA genes (4 rRNA species). A total of 83 simple sequence repeats (SSRs) were identified in the chloroplast genome. This chloroplast genome resource will be useful for the study of the evolution and genetic diversity of Angelica keiskei in the future.